Clinicopathologic Correlation of Oral Lichen Planus and Oral Lichenoid Lesions: A Preliminary Study - Marinka Mravak-Stipetić; Božana Lončar-Brzak; Iva Bakale-Hodak; Ivan Sabol; Sven Seiwerth; Martina Majstorović; Magdalena Grce (The Scientific World Journal)
Oral lichen planus (OLP) and oral lichenoid lesions (OLL) are clinically and histologically similar lesions but their treatment planning and prognosis are different. The review of the literature indicates numerous criteria to distinguish these two lesions; however there is a lot of inconsistency. Thus, the aim of this study was to determine the correlation of histopathology and clinical OLP and OLL diagnosis and to clarify which histopathologic criteria could best distinguish these two diagnoses. A retrospective study showed that clinically diagnosed 92 OLPs and 14 OLLs have been confirmed histopathologically in 52.2% and 42.9% of cases, respectively. In addition, histopathology showed statistically significant more eosinophils (P<0.0005), plasma cells (P<0.0005), and granulocytes (P<0.05) in OLL than OLP. To establish histopathological diagnosis of OLP and OLL it should be mandatory to define the type of cells in mononuclear infiltrate, which can be associated more accurately with clinical feature and patient history. Therefore, currently accepted diagnostic criteria for OLP and OLL should be modified and validated on a larger number of patients taking into account particular distinguishing histopathological features.